Facile synthesis and gas sensing properties of nanotriangular tin oxide - Deshmukh, Rupali G.; Badadhe, Satish S.; Vaishampayan, Mukta V.; Mulla, Imtiaz S. (Materials Letters, 2008)
In the present study we report a simple and convenient chemical route using pentaerythritol as a structure-directing agent for the synthesis of crystalline nanotriangular SnO2. We propose the scheme for the formation of nanotriangular structures wherein the preliminary spherical nanocrystallites are formed due to the low surface energy associated with them. These spherical nanocrystallites grow into the various linear intermediate shapes like Y, bi and tripods, which finally lead to the triangles, pyramids and bipyramids. Such variation in the structure occurs due to the structure directing pentaerythritol. These polycrystalline SnO2 nanomaterials with structural peculiarities were tested for the gas sensing characteristics. Their response towards ethanol vapor, H-2 and LPG were investigated. It was found to exhibit high response towards ethanol vapors at the operating temperature of 250 degrees C. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Nanomaterials; Oxides; Semiconductors; sensors

H(2)S gas sensitive indium-doped ZnO thin films: preparation and characterization - Badadhe, Satish S.; Mulla, Imtiaz S. (Sensors and Actuators B-Chemical, 2009)
High quality indium-doped ZnO (IZO) thin films (similar to 100 nm) have been deposited onto the glass substrates by using a conventional spray pyrolysis technique. Precursors such as zinc acetate, indium chloride with Brij-35 (polyoxyethylene lauryl ether) as a non-ionic surfactant were used. The morphology, crystal structure, elemental analysis and the gas response properties were investigated by using SEM, TEM, XRD, AFM and XPS techniques. The films show hexagonal wurtzite structure which reveal variations in (100). (00 2) and (10 1) intensities with indium doping. The crystallite size calculated by Scherrer formula was in the range of 30-50 nm. The SEM and AFM analysis show 50-70 nm sized grains, while the TEM confirms formation of grains by similar to 10nm sized particles. Their response towards various gases was measured at different operating temperatures and different levels of In-dopants. The 3 at% In-doped ZnO showed response as high as 13,000 for 1000ppm H(2)S at 250 degrees C. It exhibited fast response (similar to 2s) and recovery time (similar to 4 min). The gas response strongly depends on the morphology and indium concentration. The high gas response of IZO is explained on the basis of thickness dependent trap state density. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Hydrogen sulfide sensor; Indium oxide; Spray pyrolysis; thin film; Zinc oxide

Microwave-assisted synthesis and humidity sensing of nanostructured alpha-Fe2O3 - Deshmukh, Rupali G.; Badadhe, Satish S.; Mulla, Imtiaz S. (Materials Research Bulletin, 2009)
Nanocrystalline alpha-Fe2O3 has been prepared on a large-scale by a facile microwave-assisted hydrothermal route from a solution of Fe(NO3)(3)center dot 9H(2)O and pentaerythritol. A systematic study of the morphology, crystallinity and oxidation state of Fe using different characterization techniques. Such as transmission electron microscopy, X-ray diffraction, and X-ray photoelectron spectroscopy was performed It reveals. that nanostructured alpha-Fe2O3 comprises bundles of nanorods with a rhombohedral crystalline Structure. The individual nanorod has 8-10 nm diameter and similar to 50 nm length. The as-prepared nanostructured alpha-Fe2O3 (sensor) gives selective response towards humidity. The sensor shows high sensitivity, fast linear response to change in the humidity with almost 100% reproducibility. The sensor works at room temperature and rejuvenates without heat treatment. The as-prepared nanostructured alpha-Fe2O3 appears to be a promising humidity sensing material with the potential for commercialization. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Electrical properties; Nanostructures; Oxides; X-ray diffraction

Effect of aluminium doping on structural and gas sensing properties of zinc oxide thin films deposited by spray pyrolysis - Badadhe, Satish S.; Mulla, Imtiaz S. (Sensors and Actuators B-Chemical, 2011)
A facile spray pyrolysis route is used to deposit aluminium doped ZnO (AZO) thin films on to the glass substrates. It is observed that on aluminium doping the particle size of ZnO reduces significantly; moreover, uniformity of particle also gets enhanced. Their XRD study reveals that intensity ratio of crystal planes depend on the aluminium doping concentration. The gas response studies of; similar to 800 nm thick Al-doped ZnO films at different operating temperatures show that 5 at% Al-doped ZnO thin film exhibits highest response towards H(2)S gas at 200 degrees C. The results suggest that the gas response strongly depends on the particle size and aluminium doping in the ZnO. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Aluminium; H(2)S sensor; Spray pyrolysis; thin film; Zinc oxide

Synthesis of single crystalline CdS nanocombs and their application in photo-sensitive field emission switches - Chavan, Padmakar G.; Badadhe, Satish S.; Mulla, Imtiaz S.; More, Mahendra A.; Joag, Dilip S. (Nanoscale, 2011)
Single crystalline CdS nanocombs were synthesized by a thermal evaporation route. The photo-sensitive field emission current shows a reproducible switching behavior, with a rise in current level of nearly five times the initial preset value of similar to 1 mu A. An ultra low turn-on field, required to draw an emission current density of similar to 0.1 mu A cm(-2) (100 nA), is found to be similar to 0.26 V mu m(-1) (260 V), which is much lower than the reported values for various other CdS nanostructures. Upon illumination with visible light the CdS nanocombs act as a photo field emission switch. At an applied field of similar to 0.65 V mu m(-1) the current densities are observed to be similar to 14.6 mu A cm(-2) and similar to 26.9 mu A cm(-2), without and with light illumination, respectively. The average emission current is seen to be stable over the duration of measurement for two preset values. The high sensitivity and fast response in the visible range indicates that the CdS nanocombs can be used as a photo-sensitive field emitting switch in device applications, and also in pulsed electron beam technology.

Evaluation of n-type ternary metal oxide NiMn2O4 nanomaterial for humidity sensing - Gawli, Yogesh; Badadhe, Satish S.; Basu, Aniruddha; Guin, Debanjan; Shelke, Manjusha V.; Ogale, Satishchandra (Sensors and Actuators B-Chemical, 2014)
Synthesis of mono-dispersed oleic acid (OA) capped NiMn2O4 (NMO) nanoparticles and their use for humidity sensing is reported. Oleic acid capped NMO (NMO-cOA) nanoparticles are synthesized from nickel oleate and manganese oleate complex. NiMn2O4 is obtained by removing oleic acid capping at 500 degrees C in air. X-ray diffraction analysis shows formation of pure NiMn2O4 phase which is also confirmed by HRTEM-SAED analysis. The TEM analysis also shows that the nanoparticles are nearly mono-dispersed. Doctor bladed films of NMO nanoparticles are seen to exhibit excellent humidity sensing property. The resistivity is seen to change by two orders with humidity change from 11% RH to 92% RH with fairly good linearity over the entire range. The response and recovery times are also fast. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Humidity; Impedance; Nanoparticles; NiMn2O4; Oleic acid; Sensor

Photo-enhanced field emission studies of tapered CdS nanobelts - Chavan, Padmakar G.; More, Mahendra A.; Joag, Dilip S.; Badadhe, Satish S.; Mulla, Imtiaz S. (2014 27th International Vacuum Nanoelectronics Conference (IVNC), 2014)
Field emission and photo-enhanced field emission characteristics of single crystalline tapered CdS nanobelts have been investigated. The turn-on field for the emission current density of similar to 0.1 mu A/cm(2) is found to be similar to 2.1 V/mu m, which is much lower than reported values for various CdS nanostructures. The photo-enhanced field emission current shows a reproducible photo-switching behavior with rise in current level nearly four times that of its initial preset value (similar to 1 mu A) which is found to be very remarkable. Possible mechanism of photo-enhanced field emission is discussed.
Keywords: Current stability; field emission; Nanobelts; Photoswitching

Synthesis, microstructure, optical and field emission studies of iron vanadium oxide nanosheets - Badadhe, Satish S.; Suryawanshi, Sachin R.; Naphade, Rounak A.; Chaudhary, Minakshi V.; More, Mahendra A.; Shelke, Manjusha V.; Ogale, Satishchandra B. (Journal of Physics D-Applied Physics, 2016)
We report a single step growth of thin graphene-like, densely packed FeV3O8 (FVO) nanosheets on silicon substrates via facile hydrothermal synthesis. These nanosheets have dimensions of a few microns with thin edges, offering very high aspect ratio. These FVO nanosheets exhibit excellent field emission behaviour with low turn on and threshold voltages of 1.3 V mu m(-1) and 1.7 V mu m(-1), respectively. The corresponding emitter delivers high emission current density of (similar to 1.650 mA cm(-2)) at fairly low applied field (similar to 4.00 V mu m(-1)).
Keywords: FeV3O8; field emission; nanosheets

Facile synthesis of nanocomposites of CNF-Sn and C-Sn microspheres: Prospective field emitter - Badadhe, Satish S.; Yadav, Poonam; Suryawanshi, Sachin; More, Mahendra A. (Journal of Alloys and Compounds, 2022)
We report synthesis of Carbon nanofibers (CNFs) and hybrid nanocomposites namely, CNF-Sn and C-Sn microspheres using simple electrospinning technique, followed by annealing in controlled atmosphere. The as-prepared materials were characterized using X-raydiffraction (XRD), Field emission scanning electron microscopy (FESEM), Transmission electron microscopy (TEM), Ultra-violet photoelectron spectroscopy (UPS), and Raman spectroscopy to reveal their physico-chemical properties. As carbon family members are potential materials for field emission (FE) based applications, owing to their high aspect ratio FE characteristics of the synthesized materials were explored at base pressure of 1 x 10(-8) mbar. Interestingly, the hybrid nanocomposite CNF-Sn and C-Sn emitters showed improved FE behavior (with the turn-on field of 3.4 and 1.36 V/mu m, respectively) in contrast to the pristine CNFs emitter (turn-on field of 5.4 V/mu m). Furthermore, the maximum emission current density is substantially enhanced, 7.75 and 4.6 mA/cm(2) for CNF-Sn and C-Sn emitters, respectively. The improvement in the FE behavior of nanocomposite emitters is attributed to the combined effect of morphology and modulation of electronic properties at the interface of nanocomposites. The results confirm that FE characteristics of pristine nanostructures can be greatly improved upon formation of their nanocomposites and this approach can be extended to other nanostructures for improving their multi-functionalities. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: carbon nanofiber; electrospinning; field emission; Nanocomposite; Tin